The Use of Lesson Plan Based on Brian Tomlinsin Principle - Irma Ramayani (JADEs Journal of Academia in English Education, 2021)
The purposes of this study are to to know learning criteria based on Brian Tomlinson's Principle applied by the teacher in Teaching English. To achieve the purposes of this study, the researcher used qualitative approach with case study type by taking place at SMPN 2 Langsa and data collection techniques are from various data collection techniques, such as interviews, questionnaires and document analysis. While the data source is the subject of where the data can be obtained. The data sources in this study are person and paper. That way the teacher at SMPN 2 Langsa chose the RPP criteria based on Brian Tomlinson, namely Visual, dependent, independent and kinesthetic. Then to prove the results of the interview the author also directly evaluates students directly through documents or some questions given by the teacher. From the results of the document the writer found that students after learning using the RPP (lesson Plan) criteria based on Brian Tomlinson were able to answer very satisfying questions and even some students answered correctly all of the questions. The relationship between the principles of teaching and learning between RPP in Indonesia and abroad by Brian Tomlinson is that they have similarities in the preparation of lesson plan such as determining topics as learning references, learning objectives, time, learning media, and learning procedures.